The design and evaluation of the M-Kids mobile application to engage learning among Islamic pre-schoolers in Malaysia / Wan Irma Sabrina Idris - Wan Irma Sabrina, Idris (2022)
Recently, there has been renewed interest in the issue of providing a proper education for young children aligned with the development of the rapid technology era. This study aims at identifying the changes in cognitive and behavioural development in Islamic preschool children aged five to six years old in Malaysia upon the usage of the designed and well-developed M-Kids Mobile Learning Application prototype. Several studies have documented that technology is a forerunner in the future of learning (Keegan, J., 2016), and even in Malaysia's education system for instance, as reported by Chin (2018) in The Star Online, public schools in Malaysia are going digital with the introduction of e-textbooks starting in 2019 as announced by Deputy Education Minister. More recently, in line with helping children and youth affected by COVID-19, United Nations International Children's Emergency Fund (UNICEF) and Microsoft Corporation have announced the expansion of a global learning platform. This is before the available data from UNICEF where 1.57 billion students have been affected by school closures in more than 190 countries worldwide (Thompson, 2020). Due to this factor, a community such as parents, educators and researchers started to debate upon one question which has been concerned by the outcome of this scenario: are the technology-related practices developed appropriately for young children (Guerrero et al., 2019; Straker et al., 2018). Thus, this study, which is in response to the suggestion, set out to design and develop appropriate content in the mobile application for young children. A design-based research framework (Thomas C. Reeves., 2006) as a methodological approach was used, dividing this study into five phases with five objectives; finding the needs through needs analysis, design and evaluation of theories through thematic analysis, development of a prototype and iterative of solution through usability heuristic analysis, prototype implementation through observation and finally getting feedbacks from solutions through mobile heuristics analysis for children. 150 preschoolers from 4 Islamic Preschools in Klang Valley, Malaysia were involved in this study. The findings indicated that there were positive feedback and highly agreement from parents and teachers on the changes in preschool children’s cognitive and behavioural development towards the usage of M-Kids Mobile Learning Application in their learning. M-Kids Mobile Learning Application managed to improve the child's cognitive development by making the child understand the story, comprehend, and answer the questions given. Parents and teachers agreed that M-Kids Mobile Learning Application managed to implement moral and Islamic values in the learning content, and they approved that the usage of the application was able to practice good behaviour in the learning process. Hence, the study results represent a further step for practitioners towards developing more mobile learning content that is appropriate and beneficial to the development of young children in the future.